THE INFLUENCE OF NUTRITION SCIENCE LEARNING ON STUDENTS ON THE CONSUMPTION ATTITUDE OF TRADITIONAL GORONTALO FOOD (The Influence of Learnng Nutrition Sciences on Students to Attitudes of Gorontalo Tradisional Food Consumption) - Arifasno Napu; Irwan Irwan; Hartati Inaku; Anna Y. Pomalingo; Yuszda K. Salimi; Alimuddin Alimuddin (Jambura Journal of Health Sciences and Research, 2023)
AbstrakMakanan tradisional sudah mulai kurang dikenal dan bahkan ditinggalkan oleh generasi muda termasuk di Gorontalo. Mengantisipasinya, di Gorontalo telah dilaksanakan kebijakan pelestarian dan pengembangannya melalui mata pelajaran muatan lokal (mulok) ilmu gizi berbasis makanan tradisional Gorontalo (MTG) pada pendidikan dasar (SD,SMP) dan menengah (SMA/SMK). Kebaruan dalam penelitian ini karena meneliti tentang pembelajaran Ilmu Gizi terhadap sikap konsumsi makanan traditional Gorontalo. Tujuan penelitian ini adalah  menganalisis pengaruh pembelajaran Ilmu Gizi terhadap sikap konsumsi MTG pada siswa yang menerima mata pelajaran mulok dan tidak mulok. Metode penelitian dilakukan secara purposive ditentukan contoh SMP di kabupaten/kota yang punya kesamaan letak geografi dan tingkat akreditasi. Provinsi Gorontalo punya 6 daerah kabupaten/kota sehingga contoh sekolah berjumlah 24 SMP (12 sekolah mulok dan 12 tidak mulok) dan setiap sekolah diwakili oleh 13 contoh siswa. Penentuan contoh siswa ini secara stratified random sampling karena populasi terdiri dari siswa yang mendapat mulok dan tidak mulok.Total contoh siswa dalam penelitian ini ada 305. Hasil penelitian bahwa sikap konsumsi MTG meliputi suka dengan alasan karena penampilan, tekstur, aroma khas, cita rasa, menyehatkan dan mudah diperoleh pada siswa mulok berbeda nyata dengan tidak mulok (p0,05). Kesimpulan bahwa pembelajaran mulok ilmu gizi berbasis MTG berpengaruh pada perubahan sikap contoh siswa. Kata kunci: Pembelajaran ilmu gizi; Makanan tradisional Gorontalo; Sikap konsumsi.AbstractTraditional food has begun to be less known and even abandoned by the younger generation, including in Gorontalo. Anticipating this, in Gorontalo a policy of preservation and development has been implemented through the subject of local content (mulok) of Gorontalo traditional food-based nutrition science (MTG) in primary (SD, SMP) and secondary (SMA / SMK) education. The novelty in this study is because it examines the learning of Nutrition Science towards the attitude of traditional Gorontalo food consumption. The purpose of this study was to analyze the effect of Nutrition Science learning on the attitude of MTG consumption in students who received mulok and non-mulok subjects. The research method was carried out purposively, determining the example of junior high schools in districts/cities that have similar geographical locations and accreditation levels. Gorontalo Province has 6 districts/cities so that the example schools are 24 junior high schools (12 mulok schools and 12 non-mulok) and each school is represented by 13 examples of students. The determination of this student example is stratified random sampling because the population consists of students who get mulok and not mulok. The total number of examples of students in the study was 305. The results of the study that the attitude of MTG consumption includes liking with the reason because the appearance, texture, distinctive aroma, taste, healthy and easy to obtain in mulok students are significantly different from not mulok (p0.05). The conclusion that mtg-based nutrition science mulok learning has an effect on changing the attitudes of student examples.Keywords: Nutrition science learning; Gorontalo traditional food; Consumption attitude.